Silvicultural madness: a case from the “Scientific Forestry” initiative in the community forests of Nepal - Basnyat, B.; Treue, T.; Pokharel, R. K. (Banko Janakari, 2018)
Following a case study approach, this paper explains how scientific forest management plans were developed and implemented in community forests of a mid-hill district in Nepal. Field observations were carried over a period of two years (December 2014 to December 2016) in two community forests. User group members, forest officials, forest technicians and executive committee members were consulted. The plans were prepared simply by compiling the administrative requirements where management prescriptions were defined either based on forest technicians’ knowledge or taken directly from the guidelines with little reference to the actual site quality, management objectives, and forest stand conditions. Apart from harvesting of trees, users hardly implemented the plans’ silvicultural prescriptions and forest restoration activities. Moreover, forest officials administratively reduced the number of trees that users could harvest to around half of what the plans allow. Accordingly, forest user groups face a paradoxical forest administration that promotes timber harvesting according to so-called scientific principles, which it then brushes aside to satisfy bureaucratic demands. The study concludes that the concept of scientific forestry is merely used as a “brand” or a seemingly sound “narrative” in community forestry, while it is of little practical relevance because administrative decisions are more powerful in guiding forest management decisions. Hence, the study suggests a replacement of the current schizophrenic mix of so-called “scientific forest management” and sweeping administrative orders with adaptive management practices in community forests. Banko Janakari A Journal of Forestry Information for Nepal Special Issue No. 4, 2018, Page : 54-64